Discovery of Novel Thiophene/Hydrazones: In Vitro and In Silico Studies against Pancreatic Cancer - Goknil Pelin Coskun; Yagmur Ozhan; Vladimir Dobričić; Jelena Bošković; Rengin Reis; Hande Sipahi; Zafer Sahin; Seref Demirayak (MDPI AG, 2023)
Cancer is the disease with the highest mortality. Drug studies contribute to promising treatments; however there is an urgent need for selective drug candidates. Pancreatic cancer is difficult to treat and the cancer progresses rapidly. Unfortunately, current treatments are ineffective. In this study, ten new diarylthiophene-2-carbohydrazide derivatives were synthesized and evaluated for their pharmacological activity. The 2D and 3D anticancer activity studies suggested the compounds 7a, 7d, and 7f were promising. Among these, 7f (4.86 µM) showed the best 2D inhibitory activity against PaCa-2 cells. Compounds 7a, 7d and 7f were also tested for their cytotoxic effects on healthy cell line but only compound 7d showed selectivity. Compounds 7a, 7d, and 7f showed the best 3D cell line inhibitory effect according to spheroid diameters. The compounds were screened for their COX-2 and 5-LOX inhibitory activity. For COX-2, the best IC50 value was observed for 7c (10.13 µM) and all compounds showed significantly lower inhibition compared to standard. In the 5-LOX inhibition study, compounds 7a (3.78 µM), 7c (2.60 µM), 7e (3.3 µM), and 7f (2.94 µM) demonstrated influential activity compared to standard. Regarding molecular docking studies, binding mode of compounds 7c, 7e, and 7f to the 5-LOX enzyme were non-redox or redox types, but not the iron-binding type. As dual inhibitors of 5-LOX and pancreatic cancer cell line, 7a and 7f were identified as the most promising compounds.